Strategy To Improve Restorative Justice Services To The Community Of Makassar City (Case Study Of The Makassar District Prosecutor's Office) - A Thirta Massaguni D; Herman H; Andi Aco Agus; Ismail (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to analyze strategies for improving restorative justice services in Makassar City, focusing on the implementation of Prosecutor Regulation Number 15 of 2020. Using a qualitative descriptive approach, the research adopts Edward III’s policy implementation theory and De Vreye’s service improvement strategy model. Data were collected through observation, interviews, and documentation, and analyzed using data condensation, data display, and conclusion drawing. The findings indicate that the implementation of restorative justice faces several obstacles, including ineffective communication, limited human resources, lack of empathetic disposition among officials, and inadequate bureaucratic support. Service strategies have not been fully effective due to low public awareness and the suboptimal application of empowerment and expectation fulfillment indicators. Strengthening regulations, enhancing coordination, and building the capacity of justice officials are essential to ensure a fair, humanistic, and sustainable restorative justice service.